Dust deposition can focus light at a limited distance on photovoltaic panels. (May 2020) - Li, Xingcai; Liu, Tiansheng; Wang, Juan; Xu, Luyao; Zhang, Zhengcai
Highlight: A new perspective is proposed that particle deposition on photovoltaic panels may have an active impact on it. The focusing light effect of deposition on the PV cells is proposed. A simply method to reduce the negative effect of deposition on the PV cells is suggested. Abstract: The particles deposited on the solar panels can scatter and absorb the solar radiation, and then present some negative impact on the output performance of photovoltaic cells. By simulating the field distribution of the external electromagnetic field of particle deposition illuminated by solar radiation, it is helpful to accurately predict the impact of particles on the photovoltaic module, and then design appropriate devices to reduce its negative effect. In this paper, we present a new perspective that the deposition of particles with suitable size can focus the incoming solar radiation in the forward direction. Based on this result, we proposed a new method to reduce the negative effects of deposition on the photovoltaic system and to enhance its power output. Our numerical results show that more than 10 times stronger incoming solar radiation in the forward direction can realistically be obtained from the light focusing effect of deposition when the thickness of solar glass in existing solar panels is reduced to 1.5 mm. In addition, some special cladding structures can be designed to exploit this valuable effect to assemble more efficient photovoltaic panels.